Postclassical Narratology : Approaches and Analyses - Fludernik, Monika; Alber, Jan, 1973- (Book collections on Project MUSE., 2010)
"Postclassical narratology has reached a new phase of consolidation but also continued diversification. This collection therefore discriminates between what one could call a critical but frame-abiding and a more radical frame-transcending or frame-shattering handling of the structuralist paradigm. Postclassical Narratology: Approaches and Analyses discusses a large variety of different aspects of narrative, such as extensions of classical narratology, new generic applications (autobiography, oral narratives, poetry, painting, and film), the history of narratology, the issue of fictionality, the role of cognition, and questions of authorship and authority, as well as thematic matters related to ethics, gender, and queering. Additionally, it uses a wide spectrum of critical approaches, including feminism, psychoanalysis, media studies, the rhetorical theory of narrative, unnatural narratology, and cognitive studies. In this manner the essays manage to produce new insights into many key issues in narratology"--Publisher's description